A study of cadmium yellow paints from Joan Miró’s paintings and studio materials preserved at the Fundació Miró Mallorca - Gomez Lobon, Mar; Ghirardello, Marta; Juncosa Darder, Enric; Palomino Cabello, Carlos; Bauza, Marta; Cotte, Marine; Burnstock, Aviva; Nevin, Austin; Amato, Silvia Rita; Izzo, Francesca Caterina; Comelli, Daniela (Heritage science, 2023)
The deterioration of cadmium yellow paints in artworks by Joan Miró (1893–1983) and in painting materials from his studios in Mallorca (Spain) was investigated. Analysis of samples from Miró’s paintings and from paint tubes and palettes showed that degraded paints are composed of poorly crystalline cadmium sulfide/zinc cadmium sulfide (CdS/Cd 1−x Zn x S) with a low percentage of zinc, in an oil binding medium. Cadmium sulfates were identified as the main deterioration products, forming superficial white crusts detected using SR µXANES and µXRD techniques. Time-resolved photoluminescence measurements demonstrated that highly degraded samples display a pink/orange emission from the paint surface with a microsecond lifetime, a phenomenon observed in other degraded cadmium yellow paints. In agreement with recent studies on altered cadmium paints, these results suggest that the stability of the paint is related to its manufacturing method, which affects the degree of crystallinity of the resulting pigment. This, together with the environmental conditions in which artworks have been exposed, have induced the degradation of yellow paints in Miró’s artworks. It was finally noted that the paints exhibiting alteration in the analysed Miró artworks have a chemical composition that is very similar to the tube paint ‘Cadmium Yellow Lemon No. 1’ produced by Lucien Lefebvre-Foinet . Indeed, paint tubes from this brand were found in the studio, linking the use of this product with Miro’s degraded artworks.